2014
DOI: 10.1038/ncomms4385
|View full text |Cite
|
Sign up to set email alerts
|

The use of silk-based devices for fracture fixation

Abstract: Metallic fixation systems are currently the gold standard for fracture fixation but have problems including stress shielding, palpability and temperature sensitivity. Recently, resorbable systems have gained interest because they avoid removal and may improve bone remodelling due to the lack of stress shielding. However, their use is limited to paediatric craniofacial procedures mainly due to the laborious implantation requirements. Here we prepare and characterize a new family of resorbable screws prepared fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
134
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 172 publications
(139 citation statements)
references
References 37 publications
5
134
0
Order By: Relevance
“…Due to the relevance of swelling-induced geometrical changes for in situ application of silk 3D constructs at their final format, swelling ratio and water uptake (in percentage) were determined for silk fibroin screws of increasing molecular weight, in vitro. In accordance to what previously reported for silk materials fabricated via HFIP processing (35), silk fibroin screws had a swell ratio of ∼0.20 and a water uptake of ∼19 wt% after 72 h of hydration in PBS buffer. One-way ANOVA with Tukey's multiple-comparison test indicated that molecular weight was not statistically significantly affecting water uptake (P > 0.05).…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Due to the relevance of swelling-induced geometrical changes for in situ application of silk 3D constructs at their final format, swelling ratio and water uptake (in percentage) were determined for silk fibroin screws of increasing molecular weight, in vitro. In accordance to what previously reported for silk materials fabricated via HFIP processing (35), silk fibroin screws had a swell ratio of ∼0.20 and a water uptake of ∼19 wt% after 72 h of hydration in PBS buffer. One-way ANOVA with Tukey's multiple-comparison test indicated that molecular weight was not statistically significantly affecting water uptake (P > 0.05).…”
Section: Resultssupporting
confidence: 68%
“…3). Cylindrical specimens were evaluated through compression tests and compared with reference solid silk formats obtained through a previously reported method (35) involving the dissolution of freeze-dried, regenerated silk materials in hexafluoroisopropanol (HFIP) and the exposure of the so-formed xerogel to methanol solutions. Representative stress-strain curves of silk materials under uniaxial compression forces and compressive modulus of silk materials as a function of molecular weight are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, if these implants were instead degradable, the inflammation associated with degradation might even cause worse local problems. For instance, the new silk material is degraded enzymatically, and histological analysis demonstrated formation of fragments and particles at the surface 1 . Phagocytosable particles tend to cause inflammation, even if the material is biocompatible in bulk form.…”
Section: Standfirstmentioning
confidence: 99%
“…Interestingly, implant retainment is not regarded as a problem in the context of total joint replacements (and who would like to have a degradable hip replacement?) Perrone et al 1 argue that metal implants need removal because of stress shielding, which relates to removal of mechanical loading of the bone adjacent to the implant as a result of its placement, and subsequent bone resorption in that area due to lack of mechanical stimulation. Stress shielding under metal plates has previously been thought to necessitate early removal of the plate or the use of less stiff materials.…”
Section: Standfirstmentioning
confidence: 99%
See 1 more Smart Citation